2018
DOI: 10.1093/intqhc/mzy078
|View full text |Cite
|
Sign up to set email alerts
|

Socio-demographic determinants of women’s satisfaction with prenatal and delivery care services in Italy

Abstract: ObjectiveThe aim of this study was to examine the extent to which socio-demographic variables affect women’s satisfaction regarding antenatal and perinatal care.DesignTo take into account the role of the context in shaping women’s satisfaction, we used multilevel models, with women at the lower level, and the health districts of residence, or the hospitals in which the delivery took place, at the higher level.SettingTuscany (Italy)ParticipantsThe study is based on a representative survey focused on the satisfa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
26
2
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 52 publications
7
26
2
4
Order By: Relevance
“…One study found that vaginal delivery offered more satisfaction based on WOMBLSQ than instrumental or cesarean delivery [12]. Similar findings have been reported by other studies [69,72,73,76]. In contrast, one study found that delivery via cesarean section offered higher labor satisfaction [77].…”
Section: Plos Onesupporting
confidence: 68%
“…One study found that vaginal delivery offered more satisfaction based on WOMBLSQ than instrumental or cesarean delivery [12]. Similar findings have been reported by other studies [69,72,73,76]. In contrast, one study found that delivery via cesarean section offered higher labor satisfaction [77].…”
Section: Plos Onesupporting
confidence: 68%
“…This study's nding is similar to that of one of the few studies that used the PSQ-18 to evaluate satisfaction with non-malarial aspects of care in South-East Nigeria, where educational level signi cantly facilitated satisfaction with healthcare received [30]. Other studies conducted in Ethiopia [31] and Italy [32] which assessed maternal satisfaction with non-malarial aspects of care using a different data collection tool also highlighted education as signi cant predictors of satisfaction with care. Moving on, this study nding on satisfaction with communication and interpersonal manner of care by the health providers supports the evidence that good communication between physicians and patients has a positive impact on patient satisfaction, thereby leading to improved compliance to treatment, decreased anxiety, increased recall and understanding of healthcare [33].…”
Section: Discussionsupporting
confidence: 81%
“…However, the studies are limited and there are contradictory results about the associated factors. For example, in a study conducted in Italy, the results showed that women with a higher level of educational attainment undergoing vaginal birth were more satisfied with childbirth compared to less educated ones [21]; or a study conducted in Iran indicated that there was no correlation between mode of childbirth and level of satisfaction [22]. Also, in most of the previous studies, only a few number of possible risk factors have been investigated.…”
Section: Introductionmentioning
confidence: 99%